About the Castle of St. George - Gudavičius, Edvardas (Lietuvos istorijos studijos, 2005)
The location question of St. George’s castle, erected by the Teutonic Order (and signified by Peter Dusburg 1259), isn’t resolved. Until the last years, the predominating opinion, backed by the coincidence of settlement names, was that the fourteenth-century castle Georgenburg of the Teutonic Order stood on the same place as the castle of St. George. Now, doubts arise based on the strategic ground: at that time, the Order’s possibilities to erect a castle at such a distance were too exiguous. R. Batūra, defending the traditional opinion, doesn’t assess the war circumstances of the mid-thirteenth century. The Order, without a fleet, couldn’t erect the castle on the banks of the Nemunas there. The Livonian branch of the Order didn’t possess a reliable fleet, and the Prussian branch commenced using its fleet on the Nemunas only in the 1370s. R. Batūra’s review of the archaeology and geology of the Jurbarkas locality gives no regard to the report of Ragnit’s commendator (1406), who mentions a ruin of Georgenburg on the bank of the river Mituva (in Jurbarkas).